Protection of Family Members of the Deceased not Related by Blood or Mariage in the Law of European States - Kabza, Ewa (PRAWO i WIĘŹ, 2025)
This study aims to demonstrate, using examples from selected European jurisdictions, the extent to which persons not related by blood or marriage to the deceased are protected in the event of their death. In other words, it considers those outside the traditionally and narrowly defined family unit. This protection can be seen at several levels: they may be granted intestate succession status, a right to a fixed portion of the estate or a forced share, certain housing rights (such as the right to use the dwelling and furnishings or succeed to a tenancy upon the tenant’s death) and maintenance-type claims. It is these various forms of protection that provide the framework for the analysis.